SYSTEM PENDETEKSI KELAYAKAN KOLAM IKAN NILA MENGGUNAKAN METODE SAW (SIMPLE ADDITIVE WEIGHTING) BERBASIS IoT (INTERNET OF THINGS) - Anderias Eko Wijaya; Aldi Riyadi (STMIK SUBANG, 2021)
Tilapia (Oreochromis niloticus) is a type of freshwater fish consumption with elongated and flattened body shape laterally and blackish white color. Tilapia originated from the Nile River and surrounding lakes. Now this fish has spread to countries on five continents with tropical and subtropical climates. Whereas in cold climates, tilapia cannot live well. ideal water temperature in tilapia enlargement ponds ranges between 27.7-29.3 ° C, where fish will grow optimally at water temperatures around 25-32 ° C.for the pH of the tilapia enlargement ponds range between 6, 4-8.5 and turbidity range of 3-19 NTU, because this high turbidity level has an effect on the amount of tilapia mortality. With the system that the researchers created, it was easier to determine a suitable fish pond to maintain as a life of tilapia with the help of the Internet of Things network system and reduce the failure rate in breeding and implementation of Thingspeak as a platform to display the results of data obtained by sensors and calculated with method calculation. This system takes data with temperature sensors, pH and Turbidity, to find water temperature, acidity and alkalinity in water and turbidity of water. Then the data obtained is sent to the ESP8266 module network and sent to the thingspeak platform, the data that appears is inputted into the database to be processed using the SAW method, the results of the SAW method calculation are displayed by the system. Implementation of the SAW (Simple Additive Weighting) Method for Detecting the Feasibility of Iot-Based Fish Ponds (Internet of Things) has been successfully implemented. So that it can rank tilapia ponds based on parameters of temperature, pH, turbidity.